ADVERSE EVENTS AFTER IMMUNIZATION (AEFI) POST COVID-19 VACCINATION IN THE WORK AREA OF THE HEALTH DEPARTMENT OF SURAKARTA - Sri Hartutik; Exda Hanung Lidiana (Gaster, 2023)
Background COVID-19 pandemic was designated as a health disaster by the government of the Republic Indonesia Number 11 of 2020 concerning the Determination of a Public Health Emergency of Corona Virus Disease 2019 (COVID-19) on March 31, 2020. In tackling Covid 19, the Government has issued several policies, one of the policies that has been implemented the provision of the national covid 19 vaccination. AEFI is a follow-up event after immunization, all medical events or reactions that occur after the patient is injected with the vaccine. Objective To find out the description of post-immunization follow-up events (Aefi) after the Covid 19 vaccination in the Ministry of Health Surakarta. Methods The quantitative descriptive research method uses a simple random sampling technique with inclusion criteria. Age>18 years, has been vaccinated covid 19 for 2x and has symptoms of Aefi. Results respondents who experienced AEFI after the Covid 19 Vaccine were mostly Young Adult Age, Female gender, marital status married, history of disease/comorbid most of the respondents who experienced AEFI was mild hypertension. Conclusion Most of the AEFI symptoms felt by respondents were fever and the type of Aefi of respondents was mostly non-serious/mild.